2018
DOI: 10.1002/iub.1941
|View full text |Cite
|
Sign up to set email alerts
|

UCK2 upregulation might serve as an indicator of unfavorable prognosis of hepatocellular carcinoma

Abstract: Uridine‐cytidine kinases (encoded by UCK1, UCKL1, and UCK2) catalyze the phosphorylation of uridine and cytidine to uridine monophosphate (UMP) and cytidine monophosphate (CMP). In this study, using data from the Cancer Genome Atlas (TCGA), we analyzed the expression profile of uridine‐cytidine kinase genes in hepatocellular carcinoma (HCC), their prognostic value, and the epigenetic alterations associated with their dysregulation. Results showed that UCKL1 and UCK2, but not UCK1 were significantly upregulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 19 publications
3
25
0
Order By: Relevance
“…This peculiarity could enable UCK2 as a significant activating agent of nucleoside prodrugs, such as cyclopentenyl cytidine . Current studies have found that UCK2 is overexpressed in several types of cancer tissues and its upregulation is associated with poor progression and prognosis of breast cancer and hepatocellular carcinoma . Our study shows the high expression of UCK2 in lung cancer, especially in the early stages.…”
Section: Introductionsupporting
confidence: 53%
“…This peculiarity could enable UCK2 as a significant activating agent of nucleoside prodrugs, such as cyclopentenyl cytidine . Current studies have found that UCK2 is overexpressed in several types of cancer tissues and its upregulation is associated with poor progression and prognosis of breast cancer and hepatocellular carcinoma . Our study shows the high expression of UCK2 in lung cancer, especially in the early stages.…”
Section: Introductionsupporting
confidence: 53%
“…Consistent with the analyzed results and previous reports 40 , UCK2 up-regulation in HCCs was confirmed in our great number of clinical samples (Fig. 1C-E).…”
Section: Resultssupporting
confidence: 93%
“…Despite the similarity of their catalytic functions, the catalytic efficacy of UCK2 in uridine and cytosine is 15-20 times higher than that of UCK1 38 , suggesting that UCK2 mainly contributes to the salvage pyrimidine-nucleotide biosynthesis. UCK2 up-regulation has been detected in several types of cancers including pancreatic tumor, colorectal cancer, neuroblastoma, breast cancer, and HCCs 28,37,40 . Some recent studies have demonstrated the correlation of UCK2 with poor prognosis of HCCs 40 , but the underlying mechanism by which UCK2 contributes to HCC progression and the metabolic/non-metabolic roles of UCK2 in HCCs are largely undetermined.…”
Section: Introductionmentioning
confidence: 99%
“…However, the 5-year survival rate of patients with HCC remains low due to the high rates of local recurrence and distant metastasis ( Allemani et al, 2015 ). Several studies have demonstrated that various aberrantly expressed genes can be used to determine HCC prognosis ( Chen et al, 2018b ; Feng et al, 2019 ; Yu et al, 2019 ; Zhu et al, 2019 ). For example, low expression of CTC-297N7.9 is associated with poor prognosis in HCC patients, and could be used as an independent prognostic indicator in HCC patients.…”
Section: Introductionmentioning
confidence: 99%